The Controversial C5a Receptor C5aR2: Its Role in Health and Disease. (15th June 2017) - Zhang, Ting; Garstka, Malgorzata A.; Li, Ke
Abstract : After the discovery of the C5a receptor C5aR1, C5aR2 is the second receptor found to bind C5a and its des-arginine form. As a heptahelical G protein-coupled receptor but devoid of the intracellular G α signal, C5aR2 is special and confusing. Ramifications and controversies about C5aR2 are under debate since its identification, from putative ligands and cellular localization to intracellular signals and pathological roles in inflammation and immunity. The ruleless and even conflicting pro- or anti-inflammatory role of C5aR2 in animal models of diverse diseases makes one bewildered. This review summarizes reports on C5aR2, tries to clear up available evidence on these four controversial aspects, and delineates C5aR2 function(s). It also summarizes available toolboxes for C5aR2 study.